Invernadero ecológico a base de residuos plásticos (botellas pet) en el vivero de la ESPAM MFL. - Rodríguez Bravo, María Isabel (2018)
The objective of the research was to design an ecological greenhouse based on waste from PET bottles (polyethylene terephthalate) at ESPAM MFL nursery, showing an alternative to improve environmental problems in the reusing ways, reducing and recycling said residues. Before designing and building the greenhouse, a diagnosis was developed on the handling of plastic waste (PET bottles) in the career area, for which a survey was applied to a sample of 229 people of whom 94.76% believed that reusing PET bottles helps the environment and a 95.20 agrees to take advantage of this waste for the implementation of the greenhouse, resulting in the usual use of PET bottles, followed by a characterization that consisted of weighing for seven days the waste of PET bottles that are generated, having a total of 18.30 kg. For the design of the greenhouse model, information was collected from the wood and PET bottles and all the data of design parameters for the model was obtained, which resulted in obtaining a photorealistic 3D scheme of the greenhouse, continuously proceeding to the construction of the greenhouse using the wood for the structure and 4252 PET bottles of different sizes to cover the walls and roof. Finally, a cost study of the construction was carried out, being $ 286.50 the total value, becoming a feasible project based on the low cost and the benefits of the materials used.